CHARACTERIZATION OF LITHIUM THIN FILM BATTERY COMPONENTS PREPAREDBY DIRECT CURRENT SPUTTERING - Aziz Khan Yahya; Wagiyo H; H Jodi; E Kartini (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2013)
CHARACTERIZATION OF LITHIUM THIN FILM BATTERY COMPONENTS PREPAREDBY DIRECT CURRENT SPUTTERING. New electrolyte materials allow the design of flat lithium primary or secondary batteries for miniaturised devices from smart cards to CMOS back up. In this paper, the preparation of LiPON thin filmcomponent and an all solid-state thin filmbatteries consisting of an LiPON solid electrolyte, layered rocksalt LiCoO2 electrode, Pt and ITO current collectors, and amorphous SnO anode manufactured using sputtering and vacuum evaporation techniques is presented and discussed. The crystal structure of the LIPON thin film deposited on different substrates such as glass, Si wafer and Pt surface was characterized by X-Ray Diffractometer (XRD) method. The as-deposited cathode films are amorphous or partially crystallized. The amorphous intensity pattern appear with diffuse peaks situated at angular positions of 2θ 14º, 22º and 48º. The thin-film battery was characterized by complex impedance- and Scanning Electron Microscope (SEM) method. Cracks, which are dependent upon deposition times, are observed for the as-deposited cathode films The impedance and conductivity characteristics of the sample, do not reflect the standard characteristics of a battery. This type of behaviour could possibly be caused by the existence of a short circuit in the system configuration, so that the sample fails to generate the battery characteristics. In conclusion it could be safely assumed that the final result so far is just a multi-component system with a resistance value of 6 ohm, frequency-dependent capacitance, and a quasi Direct Current conductivity of 1.6 x 10-1 (S).